(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
Considering the centuries of colonization that the Angolan people were subjugated, which the essence of the natives was inferiorized and erased by coercive civilizing processes, there are many challenges with regard to the integration of the history and customs of its people in educational processes. We can say that one of the biggest obstacles facing Angolan education is the inclusion of national or local languages in formal education. In this article we will reflect on the importance of including different local languages in the teaching and learning processes of children in the province of Huíla-Angola. It is an analysis of Angolan and African legislation related to literacy and the teaching of traditional languages.